Pemberdayaan Masyarakat Pesisir Melalui Pengepakan Ikan Asin Menjadi Inovatif - nasib - nasib (LP3M STAI Darussalam Krempyang Nganjuk, 2021)
The purpose of this service activity is to help service partners understand the process of packing salted fish and to solve partner problems in increasing the economic value of salted fish products to become more innovative. The method used is to provide training material for salted fish packing and its application in everyday life. This is by determining a place for service partners where salted fish can be collected into one location. So that it becomes easier in the implementation of this service. The results of these service activities indicate that on average the PKK mothers have understood well how to properly package salted fish through six stages consisting of weighing fish, putting fish into packaging, pressing salted fish on a packaging press, placing salted fish on the packaging, labeling the expiration date on the package and salted fish ready to be marketed